Outdoor vs indoor physical education lessons as an opportunity to shape environmental attitudes - Marcin Pasek (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: Systematic contact with the natural environment seems to increase the level of human sensitivity to ecological problems. The purpose of the study was to assess the impact of physical activity outdoors in nature as part of school physical education on the level of environmental attitudes. Method: 220 students participated in an experimental study. The experimental group, which did exercise usually in open spaces, included 103 students. The control group, which exercised inside school, consisted of 117 students. The study period lasted two years and involved the fifth and sixth form of primary school. The authors used the part relating to attitudes in the Children's Environmental Attitude and Knowledge Scale CHEAKS in the study. Results: The appearance of eight statistically significant differences in the field of environmental attitudes in the final study in favor of the group having outdoor physical education lessons proves the cognitively and visually stimulating role of the natural environment of physically active people. The location of physical education lessons turned out to be a much stronger condition for positive environmental attitudes than gender, place of residence, parents' education level, and subjective assessment of the financial satisfaction level. Conclusion: These results are an incentive to further develop the young generation's contact with nature through outdoor physical education lessons.